Son or Daughter Care in Relation to Self-Reported Health Outcomes for Older Adults in China - Zhang, Yanan; Harper, Sarah (Frontiers in Public Health, 2022)
Objectives: Parental care in China is traditionally provided by sons. In recent decades – partly due to the One-Child Policy but also economic development and urbanisation – significant changes have occurred with more and more parents receiving care from daughters. We investigate the disparities in outcomes of eldercare provided by son(s) and daughter(s). Methods: Our study compares the self-reported health (SRH) status of parents who receive eldercare from daughters and sons in China, analysing the harmonized 2013, 2015 and 2018 waves of CHARLS with random-effects logistic estimates. Results: Our results show that the SRH of parents who receive care from their sons is greater than those cared for by their daughters. This disparity is greater in rural areas, for mothers, and poorer families. Discussion: The One-Child Policy was more effective in urban areas, reducing both the availability of sons and cultural son preference. Higher levels of education received by girls in urban settings increases their employability and thus their ability to materially care for their parents. However, traditional norms and gender differences in social economic statuses still persist in rural areas, leading to higher SRH from those cared for by sons, especially amongst those who are heavily dependent on their children — mothers or parents with less wealth.